Evaluation of defects in buildings/Pastatų defektingumo vertinimas - Janickas, Antanas (Journal of Civil Engineering and Management, 1998)
The article deals with the peculiarities of non-defective work of residential buildings, their structures and engineering systems. The concepts of the failure and limit state are defined. The causes and influences upon the failure are determined. Possible classification of damages is presented. The author defines that failure is a casual occurrence taking place in the material of the structure the points out that there are object and indirect indications of failure. The author explains that damages of structures are the result of gradual accumulation of defects under certain loading and factors due to poor quality of production, improper maintenance and design mistakes. The analytical investigations show a close interdependence of damages and expenses for removing them and the influence on the dynamics of redistribution of damages in the period of maintenance. The expressions are suggested for evaluating the possibilities of wear and failure increase. The author motivates the necessity of gathering data pertaining to the failure of buildings, structures and engineering system buildings. The forecast of non-defective work is impossible without the above-mentioned data.Article in Lithuanian.First Published Online: 26 Jul 2012